(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This paper deals with the development of time invariant distributed delay models representing the development of cohorts, i.e. group of individuals born at the same time, that develop under constant temperature, humidity, photoperiod and food conditions. Laboratory cultures of Corcyra cephalonica (Stainton) maintained in a rearing room were used for the experiments. Insects were individually reared on a standard diet and on slightly different diets with increased contents of cellulose and carboxymethyl cellulose. The developmental times, the associated variance and the survival of eggs, larvae and pupae were conducted in a thermostatic chamber with 27±1°C, 70±5% R.H. and a photoperiod 16: 8 hours (light: dark). The observations permit the parametrization of three models based on time distributed delays. The first model satisfactorily represents the emergence patterns of adults and could be useful for monitoring activities. The second model adequately represents the dynamics of eggs, larvae and pupae. In an integrated control context, this model could be used to evaluate the effect of mortality factors operating on different life stages and assist in the timing of control operations. In the third model, the development of larvae is represented by a growth based model that is parametrized with data on consumption, egestion, conversion, respiration and weight increase. The model represents not only the development of eggs, larvae and pupae but also daily food consumption and food contamination by faeces and could be used in the design of an Integrated Pest Management (IPM) program.